PENGARUH MOTIVASI INTRINSIK, KOMUNIKASI INTERPERSONAL DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA DALAM MENINGKATKAN KINERJA PEGAWAI (Kantor Kementerian Agama Kota Serang) - Hidayat, Rohmat; Kambara, Roni; Lutfi, Lutfi (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2018)
The purpose of this study was to describe the effect of intrinsic motivation, interpersonal communication and transformational leadership on job satisfaction to improve employee performance. This reserch consist of five variables, these variables were tree independent variables (exogen), one dependent variable (Endogen), and one intervening variable. The three independent variables were intrinsic motivation, interpersonal communication, and transformational leadership. Whereas, the dependent variable was employee performance, and the intervening variable was job satisfaction. This study was conducted at the Office of the Ministry of Religion in Serang Banten. The purposive sampling technique was used based on judgment sampling to 81 respondents. The primary data was collected through a checklist and open-ended questioner. Data were analyzed by Structural Equation Modelling technique using SmartPLS software. There six of Seven hypotheses that have been supported or accepted: intrinsic motivation positive and significant impact on job satisfaction, interpersonal communication positive and significant impact on job satisfaction, transformational positive and significant impact on job satisfaction, intrinsic motivation positive and significant impact on employee performance, transformational leadership positive and significant impact on employee performance, and job satisfaction positive and significant impact on employee performance. While there was one hypothesis is unsupported or rejected: interpersonal communication positive but insignificant impact on employee performance.